(untitled) (International Journal of Physiotherapy, 2023)
Background: Even though physiotherapists attempt to match care to the patient’s needs, there is little knowledge about which treatments are applied in daily practice and which treatments have the most potential to improve ROM in patients with non-specific neck pain with a limited ROM. The objective of this study was 1) to establish the measurement error of the Sensamove cervical training accelerometer (SCT); 2) to describe the applied treatments for patients with non-specific neck pain with an identified restriction in cervical Range of Motion (ROM) in primary care physiotherapy clinics; 3) to explore if the cervical ROM, pain, (perceived) disability and motor control improved after one manual therapy treatment. Methods: The standard error of measurement (SEM) and the smallest detectable difference (SDD) were calculated based on a test-retest study. Second, an explorative, longitudinal study design (follow-up one week) was performed. Inclusion criterion: nonspecific neck pain with an identified restriction in cervical ROM. Measurements: pre- (T0) and post-treatment (T1), and one-week post-treatment (T2). Outcomes: ROM, motor control movement task, Numerical Pain Rating Scale (NPRS), and Patient Specific Function Scale (PSFS). Results: The SEM varied from 1.62° (lateral flexion right) to 3.46° (extension). The SDD varied from 4.49° (lateral flexion right) to 9.58° (extension). Four physiotherapists included 24 patients and used eight different treatments. The T0-T2 improvement in cervical ROM ranged from 2.95° (SD 6.09) (right lateral flexion) to 11.00° (SD11.87) (left rotation). The movement task was performed 3.96 (SD 4.24) seconds faster. The NPRS decreased by 3.08 (SD 1.82) points, and PSFS improved by 7.71 (SD 5.34) points. Conclusion: The measurement error has been established. Moreover, this study illustrates that matched treatments, as applied in daily practice, have the potential to induce short-term improvements.